Implementation of E-Governance Through the Development of Information Technology-Based Employee Competencies at the Supreme Court Training and Leadership Center - Saanih; Suryaningsih; Saprudin; Ifan Hamzah Fansuri; Slamet Riyadi; Abdul Rahman Rasyid; Ridwan Maulana; Dion Mahendra (Catalist Indo Publisher, 2026)
Background This research analyzes the implementation of e-governance to accelerate digital transformation and build an adaptive training ecosystem at the Management and Leadership Training Center of the Supreme Court. Methods Utilizing a qualitative descriptive approach through literature study and institutional observation, the findings are mapped using four analytical frameworks: Governance, Network, Institutional, and Multi-Level. Results The study reveals that integrating systems such as SIMDIKLAT, a Learning Management System (LMS), e-assessment, and e-administration has significant potential to create an intelligent, integrated, and accountable training ecosystem. The success of this transformation heavily relies on three main pillars: intensive digital collaboration across units, the implementation of robust Standard Operating Procedures (SOPs), and seamless system interoperability. However, the implementation faces significant challenges, including uneven technological infrastructure, a digital literacy gap among staff and trainers, and complex issues related to data security and a not-yet fully adaptive work culture. Conclusions The implications of these findings are exploratory, necessitating further empirical validation and testing to measure the specific impact of each framework on training performance and effectiveness. Practically, this research recommends strategic actions, such as strengthening and equalizing technology infrastructure, aligning curricula with digital competency needs, utilizing learning analytics data for decision-making, and building strategic partnerships with various stakeholders. The originality of this study lies in its contribution of a multidimensional analytical framework specifically designed to orchestrate e-governance transformation within government training institutions—a topic still relatively rarely discussed in a holistic and integrated manner in the existing literature.